Drug abuse's RM8 billion toll on govt: Staggering cost: PM laments revenue loss - Abas, Azura (The New Straits Times Press (Malaysia) Berhad, 2014)
THE government has had to fork out huge amounts of money to fight drug abuse, with a survey conducted in 2009 revealing that a staggering RM8.65 billion was used solely for this purpose.Prime Minister Datuk Seri Najib Razak said based on Universiti Utara Malaysia's report on the economic impact of drug abuse, the government had to spend huge amounts on direct expenditure, covering enforcement and drug rehabilitation programmes as well as indirect cost covering health treatment, lost productivity and crime related costs involving 63,884 drug addicts.